2016
DOI: 10.1111/jrh.12224
|View full text |Cite
|
Sign up to set email alerts
|

Does Travel Time to a Radiation Facility Impact Patient Decision‐Making Regarding Treatment for Prostate Cancer? A Study of the New Hampshire State Cancer Registry

Abstract: Overall, further travel time to a radiation facility was not associated with lower utilization of XRT. These data are encouraging regarding access to care for CaP in New Hampshire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…While eight of the USA-based studies, reported higher incidence rates among urban residents (or those from areas with higher density of urologists) (25, 38, 40–44, 46), two found no geographical differentials (39, 45). Similarly, two Australian studies reported no significant differences (31, 54), three studies found higher prostate cancer incidence among urban males (32, 52, 53) and one study recorded the reverse pattern (55).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…While eight of the USA-based studies, reported higher incidence rates among urban residents (or those from areas with higher density of urologists) (25, 38, 40–44, 46), two found no geographical differentials (39, 45). Similarly, two Australian studies reported no significant differences (31, 54), three studies found higher prostate cancer incidence among urban males (32, 52, 53) and one study recorded the reverse pattern (55).…”
Section: Resultsmentioning
confidence: 95%
“…Of the 23 studies included, 14 (six high, eight moderate quality) reported higher prostate cancer incidence rates in urban areas (25, 32, 36, 38, 40–44, 46, 47, 49, 52, 53), two (moderate) higher rates in rural areas (50, 55) and seven (one high, six moderate) no urban rural differences (31, 37, 39, 45, 48, 51, 54) (Figure 2; Table 3). Six studies used a mixture of data collected both prior to and after the widespread use of PSA testing, which combined with varying time-periods for analysis, could lead to conflicting patterns (31, 32, 39, 49, 51, 55).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations